The U.S.-Indonesian relationship in the 1990's and beyond - Packard, Anthony M. (Monterey, California. Naval Postgraduate School, 2013)
This thesis argues that while Indonesia and the United States are not the closest of allies, new approaches to the way both countries formulate foreign policy will lead to a stronger friendship. A summary of U.S.-Indonesian relations is placed within the context of Indonesian history, so as to provide an appropriate vantage point from which to view future developments. The national goals of each country are examined next, with the belief that any improvement in bilateral relations will naturally stem from the common interests of the two countries. Where differences are noted, it is often a case of similar underlying objectives driving incongruent policies. It is in these areas that modern approaches to American foreign policy will reap the largest rewards. This thesis contends that from the political, economic, and security points of view, both the United States and Indonesia have much to gain from an improved relationship. The domestic and foreign policies of the two countries can be furthered simultaneously; first, INdonesia must soften its anti-colnoial rhetoric, and the United States must take post-Cole War approaches to formulate post-Cole-War foreign policy